Performance of Maize Varieties for Yield and Yield Attributes in Mustang, Nepal - Bhartee, Prakash; Bastola, Arjun; Rai, Pratima Bantawa; Gotame, Gaurab; Nemoto, Kasuhiro (Far Western Review, 2024)
The performance of open pollinated varieties of maize were tested with the local variety in high hills region of Nepal. Six maize varieties were tested in RCB design replicated four times during April-November of 2023 in Mustang, Nepal. Ganesh-2, Local rato, Manakamana-5, Manakamana-6, Ganesh-1 and Lumlepahelo were the six maize varieties used to evaluate the performance of different varieties of maize for yield and yield attributes. pH of research field soil was neutraland texture was sandy loam. Ear and plant height, days to 50% flowering, leaf number, cob diameter and length, grain rows number per cob and grains number per row were recorded from ten sample plants from each plot while stover and grain yield were recorded from the net plot area of 2.4 m2 during research period. The results revealed that Ganesh-1 had significantly taller height of plant at 120 days after sowing also number of leaf below main cob and main cob height from ground level was also more in Ganesh-1. Local rato was shorter in height and leaf below main cob was also significantly lowest. Days to 50 % tasseling and silking was very early in Local rato while it was very late in Ganesh-1. Cob length and diameter, kernels count per row, stover and grain yield were observed significantly higher in Ganesh-1. In terms of grain yield, Ganesh 1 was followed by Manakamana 6 and Ganesh 2. Almost all parameters were observed lowest in Local rato. Thus, it was concluded that Ganesh-1 showed the better results in terms of yield attribute and yield in the Mustang district of Nepal.